Analisis Kesalahan Berbahasa Dalam Interaksi Pembelajaran Bahasa Indonesia pada Siswa Kelas X MIPA 1 SMAN 1 Bantaeng - Reski Fadila Ruslan; Nurmiah Muin; Andi Puspitasari (Journal on Education, 2023)
This study aims to describe (1) the forms of language errors in the interaction of learning Indonesian in class X MIPA 1 students of SMAN 1 Bantaeng (2) the factors that influence language errors in the interaction of learning Indonesian in class X MIPA 1 SMAN 1 Bantaeng. The subjects of this study were all 36 students of class X at SMAN 1 Bantaeng. The objects in this study were pronunciation, diction, and sentence structure errors in group discussions about short story reading. Collecting data in this study using observation techniques, recording techniques, and note-taking techniques. The data obtained were analyzed using a qualitative descriptive analysis technique. The results of this study indicate that 52 sentences containing errors were found, namely (1) 30 pronunciation errors due to the influence of the Makassar dialect, namely phoneme changes, phoneme omissions, and phoneme additions, (2) 8 diction errors due to inadequate word selection. correct, and (3) sentence structure errors totaling 14 errors caused by limited vocabulary in delivering good and correct sentences. It is hoped that the results of this study will provide feedback to students, Indonesian language teachers, schools, other researchers, language users and related parties.